A method for comprehensive utilization of lithium-phosphorus in pyroxenite ore
By using different temperatures to cure and calcinate the lithium extraction process of phosphorus lithium aluminite, the dilute paste and equipment wall problems during the acid mixing process are solved, the lithium extraction rate is improved, and harmful gases are reduced and resource recycling is achieved.
Patent Information
- Application Number
- CN202411926160.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
In the existing methods of extracting lithium phosphate lithium aluminite, dilute paste and equipment wall problems are prone to occur during the acid mixing process, and fluoride is highly corrosive to the equipment and is unfriendly to the environment.
The method of calcining in stages of curing and calcining is adopted in different temperatures. First, the heat is insulated at 80-150℃, then the heat is raised to 200-300℃, and finally the calcination is 650-800℃. At the same time, the generated water gas and hydrogen fluoride gas are extracted through the exhaust gas port, and the alkali liquid is absorbed and recycled.
The problems of dilute paste and equipment walls during the acid mixing process are solved, the risk of equipment corrosion is reduced, the lithium extraction rate is increased by 99.42%, and the reduction of harmful gases and the recycling of resources is achieved.
Smart Images

Figure CN119735228A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium salt preparation, and in particular to a method for comprehensive utilization of lithium and phosphorus from pyroxenite ore. Background Art
[0002] Lithium is an important energy metal. China's new energy vehicles are developing rapidly, and the demand for lithium resources is also increasing. The sources of lithium include lithium extraction from brine and lithium extraction from ore. Brine reserves are abundant, but the element content is complex and the extraction is relatively difficult. Relatively speaking, lithium extraction from ore has a long history and relatively mature technology. The chemical composition of the raw materials is relatively stable, the process is easy to control, and it is relatively easy to prepare high-purity lithium products. At present, the raw materials for industrial production are spodumene, lithium feldspar, lithium mica, etc. With the gradual reduction of lithium mineral resources, the demand for lithium mineral resources is also increasing.
[0003] LiAl(PO4)(OHF) is a lithium-aluminum fluorophosphate containing Li2O=8.5%-10%. It has a high lithium content, but due to the limited resources and the special structure, it has not been industrialized. Lithium extraction from LiAl(PO4)(OHF) is mainly done by sulfuric acid method, but there are the following main problems in the process: 1. LiAl(PO4)(OHF) contains hydroxyl groups, which will generate water after acid addition, making the mixed acid material thin and paste-like and easy to agglomerate and stick to the wall during calcination; 2. LiAl(PO4)(OHF) contains fluorine, which will generate hydrofluoric acid during the mixed acid process, which is highly corrosive to equipment and unfriendly to the environment.
[0004] Related reference CN117208942A discloses a method for preparing lithium carbonate from lithium aluminum phosphate. After mixing, the materials are kept at 250-300°C for 0.5-1h and then heated to 700-800°C for calcination to obtain a calcined material. The direct calcination after keeping the temperature does not result in a stable reaction.
[0005] In view of the above problems, there is an urgent need for a method for extracting lithium from lithium aluminum phosphate with a reliable technical solution and convenient for industrial production. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for comprehensive utilization of lithium-phosphorus in phosphate-lithium aluminum ore, which can solve the problems of thin paste and equipment wall formation in the mixed acid process, reduce corrosion to the equipment, make the reaction more stable, and extract and recycle the water vapor and hydrogen fluoride gas generated in the solidification process through the waste gas port.
[0007] In order to solve the above technical problems, the present invention provides a method for comprehensive utilization of lithium-phosphorus in pyroxenite ore, comprising the following steps: S1. Grinding the pyroxene: crushing the pyroxene and grinding it into fine powder to obtain pyroxene powder; S2. Mixing: Evenly mix the fine powder of pyrophyllite and concentrated sulfuric acid to obtain a calcined mixture: S3, curing and calcining: first, keep the temperature at 80-150°C for 15-60 minutes to obtain a primary curing material, extract the water vapor and hydrogen fluoride gas generated during the curing process through the exhaust port, then heat up to 200-300°C and keep the temperature for 15-60 minutes to obtain a secondary curing material, extract the water vapor and HF gas generated during the curing process through the exhaust port, and calcine at 650-800°C to obtain a calcined material; S4, leaching of lithium-containing solution: mixing the roasted material with pure water, with a leaching liquid-to-solid ratio of 5-8:1, a leaching temperature of 60-80° C., and a leaching time of 0.5-1 h to obtain a lithium-containing leaching solution and aluminum phosphate solid; S5. Impurity removal of leachate: Add sodium hydroxide to the above lithium-containing solution to adjust the solution pH to 11-12.5, remove Fe, Al, Ca, Mg, PO4 3- Impurities get purified liquid; S6, leachate concentration: evaporate and concentrate the purified liquid to a Li2O concentration of 42-60 g / L to obtain a lithium sulfate finished liquid; S7, remove a small amount of Ca by ion exchange 2+ Mg 2+ After removing impurities, lithium sulfate refined liquid is obtained; S8. Lithium precipitation: slowly add the above refined liquid into 200-300g / L pure alkali solution to carry out lithium precipitation reaction to prepare lithium carbonate solid.
[0008] By adopting the above technical scheme, the problem of thin paste and equipment wall formation in the mixed acid process is solved by adopting the method of calcination after segmented curing at different temperatures; low-temperature curing can ensure that the mixture is in a relatively dry state, and the boiling point of hydrofluoric acid is low, which can be completely volatilized at low temperature, reducing the concentration of fluoride ions in the subsequent lithium solution and reducing the corrosion to the equipment; after low-temperature curing, high-temperature roasting can be adopted to extract lithium from phosphate lithium aluminum stone as high as 99.42%; the slag composition after lithium extraction is aluminum phosphate and silicon dioxide, which is a high-quality raw material for extracting Al and P. During the curing process, the water vapor and hydrogen fluoride (HF) gas generated are promptly extracted through the exhaust port, and absorbed and recycled with alkali solution. This measure not only reduces the emission of harmful gases, but also realizes the effective utilization of resources, which meets the requirements of environmental protection and sustainable development.
[0009] Preferably, in step S1, the size of the apatite powder is ≥100 mesh.
[0010] By adopting the above technical solution, in the subsequent lithium-containing solution leaching step, the fine phosphate lithium aluminum powder can be more effectively dissolved in water, releasing more lithium ions and improving the leaching effect.
[0011] Preferably, in step S2, the weight ratio of phosphate lithium aluminum stone powder to concentrated sulfuric acid is 2:1 to 0.5.
[0012] By adopting the above technical solution, within this ratio range, the reactants can interact with each other more effectively, ensuring sufficient contact and reaction between the reactants, thereby improving the reaction efficiency.
[0013] Preferably, in step S3, curing and calcining, the temperature is first raised to 80-150°C and kept for 15-30 minutes, then raised to 200-300°C and kept for 15-30 minutes, and then continued to be raised to 650-800°C and calcined for 0.5-1 hour.
[0014] By adopting the above technical solution, under the premise of ensuring that the reaction is fully carried out, the insulation time can be appropriately shortened by 15min-30min, which can accelerate the reaction rate, improve the reaction efficiency, and improve the overall production efficiency.
[0015] Preferably, the water vapor and hydrogen fluoride gas generated during the curing process are discharged through the waste gas outlet and absorbed by alkaline solution for recycling.
[0016] By adopting the above technical solution, during the curing process, the water vapor and hydrogen fluoride (HF) gas generated are promptly extracted through the exhaust port and absorbed and recycled with alkaline solution. This measure not only reduces the emission of harmful gases, but also realizes the effective utilization of resources, which meets the requirements of environmental protection and sustainable development.
[0017] Preferably, in step S3, the primary curing temperature is 120°C and the time is 30 min; the secondary curing temperature is 250°C and the time is 30 min; and the calcination temperature is 800°C and the time is 60 min.
[0018] By adopting the above technical solution and using such time and temperature points, each stage of the reaction process can be controlled more accurately, making the reaction more stable and efficient.
[0019] Preferably, in step S4, the solid-liquid ratio is 7:1, the leaching temperature is 70° C., and the leaching time is 0.5 h.
[0020] By adopting the above technical solution and optimizing the leaching conditions, the impurity content can be effectively reduced, providing more favorable conditions for the subsequent impurity removal and lithium precipitation steps, and improving the recovery rate and purity of lithium. The leaching temperature of 70°C is a more suitable temperature point, which can ensure that the chemical reaction proceeds at a faster rate while avoiding the increase in energy consumption and equipment corrosion caused by excessive temperature. The setting of the leaching time of 0.5h shortens the production cycle and improves the overall production efficiency while ensuring the leaching effect.
[0021] Preferably, in step S5, the pH of the solution after adding sodium hydroxide is 12.
[0022] By adopting the above technical solution, when the pH value reaches 12, the removal efficiency of Fe, Al, Ca, Mg, and PO4³⁻ impurities is higher, because the solubility of hydroxide is lower at this time and it is easier to form precipitation, thereby obtaining a higher purity lithium sulfate refined liquid.
[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adopts a method of calcining after curing at different temperatures. During curing and calcining, the material is first kept at 80-150°C for 15-60 minutes to obtain a primary cured material, then the temperature is raised to 200-300°C for 15-60 minutes to obtain a secondary cured material, and the temperature is further raised to 650-800°C for calcining to obtain a calcined material, thereby solving the problems of thin paste and equipment wall formation during the acid mixing process; low-temperature curing can ensure that the mixed material is in a relatively dry state, and the boiling point of hydrofluoric acid is relatively low, so that the mixed material can be completely volatilized at a low temperature, thereby reducing the fluoride ion concentration in the subsequent lithium solution and reducing the corrosion to the equipment; high-temperature calcination after low-temperature curing can increase the lithium extraction rate of the lithium aluminum phosphate to as high as 99.42%; the slag components after lithium extraction are aluminum phosphate and silicon dioxide, which is a high-quality raw material for extracting Al and P.
[0024] 2. The present invention increases the temperature in stages and controls the appropriate holding time, which can make the reaction more stable and reduce energy consumption. Compared with direct high-temperature calcination, this step-by-step curing method can more effectively utilize heat energy and reduce energy consumption costs.
[0025] 3. In the curing process of the present invention, the water vapor and hydrogen fluoride (HF) gas generated are promptly extracted through the exhaust port and absorbed and recycled by alkaline solution. This measure not only reduces the emission of harmful gases, but also realizes the effective utilization of resources, which meets the requirements of environmental protection and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a diagram of lithium extraction slag from lithium aluminum phosphate in the present invention. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described below through specific embodiments. Example
[0028] A method for comprehensive utilization of lithium-phosphorus in pyroxenite ore comprises the following steps: S1. Grinding the pyroxene: crushing the pyroxene and grinding it into fine powder to obtain pyroxene powder; S2. Mixing: Evenly mix the fine powder of pyrophyllite and concentrated sulfuric acid to obtain a calcined mixture: S3, curing and calcining: divided into three steps, firstly, keep the temperature at 80-150℃ for 15min-60min to obtain the primary curing material, extract the water vapor and hydrogen fluoride gas generated during the curing process through the exhaust port, then heat up to 200-300℃ and keep the temperature for 15-60min to obtain the secondary curing material, extract the water vapor and HF gas generated during the curing process through the exhaust port, calcine at 650-800℃ to obtain the calcined material; heating up in stages and controlling the appropriate heat preservation time can make the reaction more stable and reduce energy consumption. Compared with direct high-temperature calcination, this step-by-step curing method can more effectively utilize thermal energy and reduce energy consumption costs.
[0029] S4, leaching of lithium-containing solution: mixing the roasted material with pure water, with a leaching liquid-to-solid ratio of 5-8:1, a leaching temperature of 60-80° C., and a leaching time of 0.5-1 h to obtain a lithium-containing leaching solution and aluminum phosphate solid; S5. Impurity removal of leachate: Add sodium hydroxide to the above lithium-containing solution to adjust the solution pH to 11-12.5, remove Fe, Al, Ca, Mg, PO4 3- Impurities get purified liquid; S6, leachate concentration: evaporate and concentrate the purified liquid to a Li2O concentration of 42-60 g / L to obtain a lithium sulfate finished liquid; S7, remove a small amount of Ca by ion exchange 2+ Mg 2+ After removing impurities, lithium sulfate refined liquid is obtained; S8. Lithium precipitation: slowly add the above refined liquid into 200-300g / L pure alkali solution to carry out lithium precipitation reaction to prepare lithium carbonate solid.
[0030] The method of calcination after staged curing at different temperatures is adopted to solve the problems of thin paste and equipment wall in the mixed acid process; low-temperature curing can ensure that the mixture is in a relatively dry state, and the boiling point of hydrofluoric acid is low, which can be completely volatilized at low temperature, reducing the concentration of fluoride ions in the subsequent lithium solution and reducing the corrosion to the equipment; after low-temperature curing, high-temperature roasting can be adopted to extract lithium from phosphate lithium aluminum stone as high as 99.42%; the slag after lithium extraction is composed of aluminum phosphate and silicon dioxide, which is a high-quality raw material for extracting Al and P, and has a high recycling value. During the curing process, the water vapor and hydrogen fluoride (HF) gas generated are promptly extracted through the exhaust port and absorbed and recycled with alkali solution. This measure not only reduces the emission of harmful gases, but also realizes the effective utilization of resources, which meets the requirements of environmental protection and sustainable development.
[0031] In step S1, the size of the pyroxenite powder is ≥ 100 mesh. The smaller the particle size of the pyroxenite powder, the larger its specific surface area and the larger its contact area with the concentrated sulfuric acid reactant, thereby improving the efficiency of the chemical reaction. In the subsequent lithium-containing solution leaching step, the fine pyroxenite powder can be more effectively dissolved in water, releasing more lithium ions, thereby improving the leaching effect.
[0032] In step S2, the weight ratio of phosphate lithium aluminum stone powder to concentrated sulfuric acid is 2: 1 to 0.5. Within this ratio range, the reactants can interact more effectively, ensuring sufficient contact and reaction between the reactants, thereby improving the reaction efficiency.
[0033] In step S3, the curing and calcining process is divided into three steps. First, the temperature is raised to 80-150°C for 15min-30min, then the temperature is raised to 200-300°C for 15min-30min, and then the temperature is raised to 650-800°C for calcining for 0.5-1h. The water vapor and hydrogen fluoride gas generated during the curing process are discharged through the exhaust port and absorbed and recycled with alkali solution. It is more preferred that the primary curing temperature is 120°C and the time is 30min; the secondary curing temperature is 250°C and the time is 30min, and the calcining temperature is 800°C and the time is 60min. Heating in stages and controlling the appropriate insulation time can make the reaction more stable and reduce energy consumption. Compared with direct high-temperature calcination, this step-by-step curing method can more effectively utilize thermal energy and reduce energy consumption costs. On the premise of ensuring that the reaction is fully carried out, the insulation time is appropriately shortened to 15min-30min, which can accelerate the reaction rate, improve the reaction efficiency, and improve the overall production efficiency. During the curing process, the water vapor and hydrogen fluoride (HF) gas generated are promptly extracted through the exhaust port and absorbed and recycled with alkaline solution. This measure not only reduces the emission of harmful gases, but also realizes the effective utilization of resources, which meets the requirements of environmental protection and sustainable development.
[0034] In step S4, the leaching solid-liquid ratio is 5 to 8:1, the leaching temperature is 60-80°C, and the leaching time is 0.5-1h. More preferably, the solid-liquid ratio is 7:1, the leaching temperature is 70°C, and the leaching time is 0.5h. The impurity content in the leachate is one of the key factors affecting the quality of subsequent products. By optimizing the leaching conditions, the impurity content can be effectively reduced, providing more favorable conditions for subsequent impurity removal and lithium precipitation steps, and improving the recovery rate and purity of lithium. The leaching temperature of 70°C is a more suitable temperature point, which can ensure that the chemical reaction proceeds at a faster rate while avoiding the increased energy consumption and equipment corrosion caused by excessive temperature. The setting of the leaching time of 0.5h shortens the production cycle and improves the overall production efficiency while ensuring the leaching effect.
[0035] In step S5, the pH value of the solution after adding sodium hydroxide is more preferably pH = 12. At this pH value, sodium hydroxide can react with Fe, Al, Ca, Mg, PO4 3- The impurities react chemically to form insoluble precipitates, thereby effectively removing these impurities from the solution. Especially when the pH value reaches 12, the removal efficiency of these impurities is higher, because the solubility of hydroxide is lower at this time, and it is easier to form precipitation, thereby obtaining a higher purity lithium sulfate refined solution. And when the pH value is 12, while effectively removing impurities, it prevents too much lithium from precipitating in the form of lithium hydroxide, making the impurity removal process more stable and controllable, helping to reduce fluctuations and uncertainties in the production process, and improving product quality and production efficiency. Example 1
[0036] After 300g of phosphate lithium aluminum stone powder and 100g of sulfuric acid are mixed evenly, the temperature is first raised to 100℃, kept warm for 30min, then raised to 200℃, kept warm for 30min, and then raised to 750℃, kept warm for 30min. The solid-liquid ratio of the calcined material to water is 6:1. After leaching at 70℃ for 30min, 1750mL of lithium-containing solution with Li2O=11.6g / L is obtained by filtration. Sodium hydroxide is added to adjust the solution pH=11.5, and then filtered and concentrated to 390ml of lithium sulfate solution with Li2O=52g / L. 7g of sodium carbonate is added, stirred and filtered, and then after ion exchange, 425mL of pure alkali solution with a concentration of 252g / L is added dropwise to precipitate lithium. The precipitation temperature is 95℃, 5g of battery-grade lithium carbonate is added as a seed, and the dropping time is 30min. After the dropping is completed, it is kept warm for 5min, and 38.8g of lithium carbonate solid is obtained after filtering and washing. Example 2
[0037] After 300g of phosphate lithium aluminum stone powder and 120g of sulfuric acid are mixed evenly, the temperature is first raised to 110℃, kept warm for 30 min, then raised to 200℃, kept warm for 30min, and then raised to 750℃, kept warm for 30 min. The solid-liquid ratio of the calcined material to water is 7:1. After leaching at 70℃ for 30min, 2080mL of lithium-containing solution with Li2O=9.9g / L is obtained by filtration. Sodium hydroxide is added to adjust the solution pH to 11.5, and then filtered and concentrated to obtain 410mL of lithium sulfate solution with Li2O=50g / L. 5g of sodium carbonate is added, stirred and filtered, and then after ion exchange, 430mL of pure alkali solution with a concentration of 255g / L is added dropwise to precipitate lithium. The lithium precipitation temperature is 95℃, 5g of battery-grade lithium carbonate is added as a seed, and the dropping time is 30min. After the dropping is completed, it is kept warm for 5min, and 36.5g of lithium carbonate solid is obtained after filtering and washing. Example 3
[0038] After 300g of phosphate lithium aluminum stone powder and 100g of sulfuric acid are mixed evenly, the temperature is first raised to 120℃, kept warm for 30min, then raised to 250℃, kept warm for 30min, and then raised to 800℃, kept warm for 30min. The solid-liquid ratio of the calcined material to water is 7:1. After leaching at 70℃ for 30min, 2050mL of lithium-containing solution with Li2O=10.1g / L is obtained by filtration. Sodium hydroxide is added to adjust the solution pH=12, and then filtered and concentrated to obtain 390mL of lithium sulfate solution with Li2O=53g / L. 7g of sodium carbonate is added, stirred and filtered, and then after ion exchange, 435mL of pure alkali solution with a concentration of 252g / L is added dropwise to precipitate lithium. The lithium precipitation temperature is 95℃, 5g of battery-grade lithium carbonate is added as a seed, and the dropping time is 30min. After the dropping is completed, it is kept warm for 5min, and 36.4g of lithium carbonate solid is obtained after filtering and washing.
[0039] The lithium carbonate products obtained in Examples 1-3 were sampled and analyzed, and the contents of the components in the samples were as follows: project Example 1 Example 2 Example 3 <![CDATA[Li2CO3]]> 99.75% 99.8% 99.86% Na 0.012% 0.014% 0.013% Cl 0.0006% 0.0007% 0.0005% K 0.0001% 0.0003% 0.0004% Ca 0.0005% 0.0005% 0.0006% Mg 0.0005% 0.0003% 0.0003% Fe 0.0001% 0.0001% 0.0001% <![CDATA[SO4 2- ]]> 0.0058% 0.0053% 0.0051% <![CDATA[PO4 3- ]]> - - - <![CDATA[F - ]]> - - - Zn 0.0001% 0.0001% 0.00002% Mn 0.0001% 0.0001% 0.00001% Al 0.0007% 0.0004% 0.0002% Cu 0.0001% 0.0001% 0.0001% Si 0.0003% 0.0001% 0.0001% It can be seen from the above table that the lithium carbonate solid prepared by the lithium-phosphorus comprehensive utilization method of pyroxenite ore in the preparation method of the present invention is battery-grade lithium carbonate.
[0040] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for comprehensive utilization of lithium-phosphorus from pyroxenite ore, characterized in that: The following steps are involved: S1. Grinding the pyroxene: crushing the pyroxene and grinding it into fine powder to obtain pyroxene powder; S2. Mixing: Evenly mix the fine powder of pyrophyllite and concentrated sulfuric acid to obtain a calcined mixture: S3, curing and calcining: first, keep the temperature at 80-150°C for 15-60 minutes to obtain a primary curing material, extract the water vapor and hydrogen fluoride gas generated during the curing process through the exhaust port, then heat up to 200-300°C and keep the temperature for 15-60 minutes to obtain a secondary curing material, extract the water vapor and HF gas generated during the curing process through the exhaust port, and calcine at 650-800°C to obtain a calcined material; S4, leaching of lithium-containing solution: mixing the roasted material with pure water, with a leaching liquid-to-solid ratio of 5-8:1, a leaching temperature of 60-80° C., and a leaching time of 0.5-1 h to obtain a lithium-containing leaching solution and aluminum phosphate solid; S5. Impurity removal of leachate: Add sodium hydroxide to the above lithium-containing solution to adjust the solution pH to 11-12.5, remove Fe, Al, Ca, Mg, PO4 3- Impurities get purified liquid; S6, leachate concentration: evaporate and concentrate the purified liquid to a Li2O concentration of 42-60 g / L to obtain a lithium sulfate finished liquid; S7, remove a small amount of Ca by ion exchange 2+ Mg 2+ After removing impurities, lithium sulfate refined liquid is obtained; S8. Lithium precipitation: slowly add the above refined liquid into 200-300g / L pure alkali solution to carry out lithium precipitation reaction to prepare lithium carbonate solid.
2. The method for comprehensive utilization of lithium-phosphorus in pyroxenite ore according to claim 1, characterized in that: In the step S1, the size of the pyroxenite powder is ≥100 mesh.
3. The method for comprehensive utilization of lithium-phosphorus in pyroxenite ore according to claim 1, characterized in that: In the step S2, the weight ratio of the phosphate lithium aluminum stone powder to the concentrated sulfuric acid is 2:1-0.
5.
4. The method for comprehensive utilization of lithium-phosphorus in pyroxenite ore according to claim 1, characterized in that: In the step S3, the curing and calcining are first heated to 80-150°C and kept for 15-30 minutes, then heated to 200-300°C and kept for 15-30 minutes, and then continued to heat to 650-800°C and calcined for 0.5-1 hour.
5. The method for comprehensive utilization of lithium-phosphorus in pyroxenite ore according to claim 4, characterized in that: The water vapor and hydrogen fluoride gas generated during the curing process are discharged through the exhaust port and absorbed by alkali solution for recycling.
Citation Information
Patent Citations
Method for preparing lithium carbonate from amblygonite
CN117208942A
Cited By
Method for extracting lithium from amblygonite
CN122147093A